PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA POWTOON TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK SD - Nadia Sahilah; Fatkhur Rohman; Fadhilah Khairani; Frida Destini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem of this research was the low learning outcomes of fifth-grade students due to the teacher's lack of use of varied learning models and media in the teaching process. This study aimed to analyze and describe the effect of the problem-based learning (PBL) model assisted by Powtoon media on students' learning outcomes in IPAS (Science and Social Sciences) subjects. This research used a quantitative method with a quasi-experimental design. The population and sample of the study were fifth-grade students of SD Negeri 1 Banding Agung, totaling 46 students. Data collection techniques included tests, observation sheets, and documentation. The hypothesis was tested using simple linear regression with the result Fcount ≥ Ftable (39.559 ≥ 4.30). Therefore, it could be concluded that there was a significant effect of the problem-based learning model assisted by Powtoon media on the IPAS learning outcomes of fifth-grade students at SD Negeri 1 Banding Agung.